Acquired Antibody to Factor XI in a Patient with Congenital Factor XI Deficiency - Stern, David M. (1982)
The results of studies in a patient with congenital deficiency of Factor XI who developed an inhibitor are presented. The patient presented with a severe, apparently spontaneous bleed into the thigh, which progressed despite infusion of fresh frozen plasma, but which responded promptly to activated prothrombin complex. During therapy with plasma his clotting time and Factor XI level were unresponsive and a Factor XI inhibitor titer of 6,000 U/ml was attained. The inhibitor was isolated and found to be polyclonal immunoglobulin G (IgG), predominantly of subclass 4. The specificity of the antibodies for Factor XI was shown by the ability of isolated inhibitor bound to polyacrylamide beads to remove Factor XI selectively from normal plasma. The binding of (125)I-labeled factor XI to the inhibitor was studied and an affinity constant of 1.65 × 10(10) liter/mol was found. Complexing of the antibodies with Factor XI was shown to block multiple activities of the clotting factor. Factor XI complexed with antibody did not bind to high molecular weight kininogen or undergo activation and cleavage by two-chain Factor XII. The complex of activated Factor XI with inhibitor prevented the cleavage and activation of Factor IX. Hence the inhibitor appears to act by binding to multiple sites on the Factor XI molecule and preventing its interaction with other molecules. Clinically these interactions of the inhibitor with Factor XI result in a state of severe Factor XI deficiency. The clinical circumstances of the case, with severe hemorrhage refractory to plasma infusion but readily responsive to an alternate clot-promoting agent, suggest that a defect of intrinsic system activation was critical, supporting the inference that Factor XI does participate in normal hemostasis. The clinical course of this patient, who has only had two documented hemorrhages in the presence of the inhibitor, is not as severe as that of patients with severe Factor VIII or IX deficiency. This suggests that physiologic activation of Factors XI and IX does not occur exclusively in series because deficiency of factors XII, XI, VIII, and IX should then have similar hemostatic consequences. We propose that independent mechanisms for bypass of Factors XII and XI are important in physiologic activation of coagulation.